Implementation of Multi-Objective Evaluation Method in Public Debt Risk Management - Jelena Stankevičienė; Sergej Rosov (Entrepreneurial Business and Economics Review, 2013)
The paper is devoted to propose a public debt risk assessment model, which allows predicting country's economic well-being trends. The proposed model evaluates different aspects of public debt-related structural indicators. Evaluation of research results enables to use multi-objective evaluation method to determine the risk of public debt. The data analysis indicates EU's ability to cope with the increasing level of public debt and predict long term fiscal consequences.